Relationships between activity and well‐being in people with parkinson's disease. Issue 5 (16th April 2018) - Ehlen, Felicitas; Schindlbeck, Katharina; Nobis, Lisa; Maier, André; Klostermann, Fabian
Abstract: Objectives: The complex symptomatology of Parkinson' disease (PD) usually goes along with reduced physical activity. Previous studies have indicated positive effects of activating therapies on patients' well‐being. This study, therefore, examined how activity in daily life is related to patients' subjective condition. Materials and Methods: Twenty‐one PD patients rated their condition every two hours during two routine days and documented the duration and type of their activities (based on the PRISCUS‐Physical Activity Questionnaire) during the respective time intervals. They were furthermore assessed regarding motor and nonmotor symptoms, personality factors, and coping strategies. Results: Patients spent on average 8.59 ± 2.93 hr per day at physical rest and 5.47 ± 2.93 hr physically active. We found highly significant associations between positive condition ratings (such as happiness, motivation, and concentration) and the duration of subsequent physical activities ( adj.r 2 = .689) as well as between the duration of these activities and a subsequent improvement in the subjective condition ( adj.r 2 = .545). This was strongest in patients using active coping strategies and showing agreeable and conscientious personality traits ( adj.r 2 = .380). Nonmotor symptom severity was weakly inversely related to the daily amount of activities ( adj.r 2 = .273), whereas no significant association with motor symptom severity was found. Conclusions: The results suggest a feedback process between a positive subjective condition and physical activities in PD patients. This appears to depend on the use of active coping strategies and nonmotor symptoms rather than on motor symptom severity. The results should encourage physicians to address the importance of everyday physical activities and to provide patients with behavioral advice. Abstract : The study investigated the interplay between everyday physical activity, self‐perception, and personality factors among twenty‐one patients with Parkinson's disease. The results indicated a feedback process between a positive self‐evaluation and physical activities. This appears to depend on the use of active coping strategies rather than motor symptom severity.